Does the Government Effectively in Optimizing Open Data? Analysis "Jago Data" in Yogyakarta Municipality - Al Fauzi Rahmat; Achmad Nurmandi; Dian Suluh Kusuma Dewi; Salahuddin Salahuddin (Journal of Governance, 2019)
Open Government Data (OGD) is a database produced by the government that can be freely accessed, used or modified, therefore, this is a support to increase transparency and public participation. This article aims to analyze the effectively optimizing Open Government Data on the Jogja Go Open Data “JAGO DATA” in Yogyakarta Municipality. Furthermore, the methodology of this article uses qualitative research with in-depth interviews and literature, moreover, the variables of this research are focused on legal guidelines and frameworks (crosstab query is 47.5%), the ability of web portal system (crosstab query is 27.5%), and human resource in government and its attitude (crosstab query is 25%), therefore, its data findings were analyzed with Nvivo 12 plus software. The result of this article shows that the Yogyakarta city government successfully implemented JAGO DATA to support transparency, accountability, and encourage public participation, moreover, it is has implemented directives regarding Open Data regulation and its innovation designed with a collaborative among regional-level work units (SKPD). Therefore, the JAGO DATA portal is rated as user-friendly with the model used at the information stage and its maturity of a web portal is still in the pre-adoption level.